Demonopolization SOEs Policy as An Efforts To Restructured Roles and Institutions in Facing Global Competition - Putu Samawati (Bappenas Working Papers, 2019)
This article discusses how SOEs prepare themselves in an effort to deal with economic globalization over the demonopolization policy. Demonopolization is a policy undertaken by the government as a commitment to implementing free trade required WTO. Economic globalization is a condition that will not be able to be avoided, a sure step that must be taken by the government is to prepare for the resilience of the nation's economy through institutional strengthening strategies. One of them is by improving the performance of SOEs through policies that can create a synergy of effort and will be able to improve the quality to face competition globally. Create competitors to SOEs will be able to encourage SOEs to improve their institutions internally and externally, this condition is one of the strategies to create professional and independent SOEs, in order to face global challenges. Restructuring of SOEs by applying corporate culture and implement of concept good corporate governance is a strategy for internal institutional reform, internal institutional strengthening will have an impact on external institutional which will provide the best service for consumers and public. The Concept of SOEs performance must be based on the principles of economic democracy that promote fair efficiency for all economic actors, the main aim of providing protection for the people of Indonesia.